Reformulations and Terminological Representations in Javier Hervada's Philosophy of Law - Mora Altamirano, Eduardo (Ius Humani. Jornal do direito, 2025)
The article aims to propose a series of redefinitions of Hervadian theory of justice and law. It does not imply modifications that affect its essence, but rather ways of formulating or terminology. To this end, six elements of Hervadian theory of justice and law are presented, trying to be faithful to the author studied, and then introducing certain variations or additional elements that could represent a small modification, or an expansion, development or projection of Javier Hervada's original theory. Methodologically, it starts from an exposition of the doctrine of the Spanish author in each thematic point discussed, to at some point address those reformulations or terminological variations.